Healthcare mosque-based information system: Planning and implementation - Ali, Hindh; Hassan, Azizah; Nakkazi , Rukia; Ahmad Dahlan, Abdul Rahman (2011)
Nowadays, the importance attached to healthcare Service provision has had many organizations utilize collaborative information systems to share health related information. It is a common trend to find information systems which store and share health related information of patients, their diagnosis and general other health information. In this paper we propose a framework for the implementation of a mosque-based healthcare Information System which attempts to enhance the function of a mosque beyond the religious border. Our aim is to develop this web-based collaborative system so as to integrate the traditional function of a mosque with professional involvement in an issue that is utmost important to any community, healthcare.Basing on the mosque’s rich functions, this study intends to strengthen the collaboration between mosques and different health organizations in order to deliver indelible community healthcare services in Malaysia.